Discipline Character Development Strategy for Madrasah Ibtidaiyah Al-Maarif Bojongsari Students - Pamuji, Slamet; Mulyadi, Yadi (PT. Riset Press International, 2024)
Madrasas contribute to introducing, growing, maintaining and improving students' disciplinary values, including compliance with madrasa rules and regulations. Apart from that, teachers also have a big role in cultivating self-discipline in their students. The aim of this research is to reveal strategies as well as supporting and inhibiting factors for developing students' disciplinary character at Madrasah Ibtidaiyah Al-Ma'arif Bojongsari Kedungreja, Cilacap, using a qualitative case study type approach. Data obtained through interviews, observation, documentation studies and literature studies. The results of the research are First, developing the disciplined character of students at Madrasah Ibtidaiyah Al-Ma'arif Bojongsari Kedungreja, Cilacap, using several approaches including routine activities, spontaneous activities, exemplary activities and conditioning activities. Second, the obstacles faced by madrasas in developing students' disciplined character consist of: teacher delays before the first period, dependence on class teachers in reading prayers at the beginning and end of lessons, student tardiness for various reasons. The solution to these obstacles, the madrasa head as the head of the madrasa is expected to be able to provide good direction and information to all madrasah residents, motivate teachers to come on time so that they both strengthen order and discipline and service to the madrasa, the madrasa head can empower teachers who others who have competence regarding reading prayers so that their implementation is better, and it is necessary to provide sanctions that have been determined by the madrasah for students who arrive late, accompanied by providing direction and information as well as motivating them to come to the madrasah early.